TINJAUAN YURIDIS PENETAPAN LOKASI PADA PENGADAAN TANAH DALAM SKALA KECIL - Rachmatika Lestari; Safrida Safrida; Phoenna Ath Thariq; Yuhdi Fahrimal (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
Land acquisition is a way to acquire land for development in the public interest. Land acquisition arrangements in Law Number 2 of 2012 concerning Land Procurement for Development in the Public Interest. Article 1 number 2 of the law stipulates that: